Determination of antioxidant potential of Nepeta nuda subsp. lydiae - Aras, A.; Dogru, M.; Bursal, Ercan (Taylor and Francis Ltd., 2016)
The antioxidant activities of ethanol and water extracts of Nepeta nuda subsp. lydiae leaves were determined by different in vitro methods such as; DPPH, ABTS, FRAP and CUPRAC assays. The results were compared to BHA, BHT and ascorbic acid as standard antioxidant compounds. Both water and ethanol extracts presented high antioxidant potential on DPPH free radical scavenging assay and CUPRAC assay. Also, both extracts presented low level on ABTS and FRAP assays. In conclusion, leaves of N. nuda subsp. lydiae have some potential of antioxidant activities, so it could be a useful source for food industry as a food ingredient after analyzing other biological properties. © 2016 Har Krishan Bhalla & Sons.
Keywords: Antioxidant Activity; Lamiaceae; Nepeta Nuda; Radical Scavenging